Monitoring Serum Creatinine, Blood Urea Nitrogen in Patients Brain Injury with Mannitol Therapy - Sari, Erni A; Suharjono, Suharjono; Wahyuhadi, Joni (Folia Medica Indonesiana, 2020)
Increased intracranial pressure is a further effect of brain injury due to structural damage and osmotic and water imbalances (Edema). Mannitol works in the proximal tubules and mannitol in the absorption of tubular cells by the mechanism of pinocytosis. The fluid transfer will draw fluid into the intracellular, so that the cell will be switched and broke. This phenomenon is referred to as the phenomenon of "Nephrosis Osmotic", in which mannitol administration may occur as a result of accumulation of drugs in the kidneys due to prolonged exposure to mannitol in the kidney and given dosage. The effects of osmotic diuresis occurring plus the dose and duration of mannitol administration are reported to cause renal function disorders (Scr and BUN). The aim of this study was to analyze changes in serum creatinine and BUN in patients with brain injury from before receiving mannitol therapy and during mannitol treatment. From the results of the study the number of patients who met the inclusion criteria, 32 patients. Serum creatinine, the initial average of 0.85 ± 0.17 mg / dl and the last day of the mean SCr 0.74 ± 0.30 mg / dl. While the mean BUN (Blood Urea Nitrogen) was 11.27 ± 2.75 mg / dl and the mean last day was 17.08 mg / dl ± 8.59 mg / dl. From Serum Creatinine and BUN data it can be concluded that there is no significant change.